Dynamics of structure and severity of dentoalveolar anomalies on the background of early orthodontic treatment during occlusion - E. E. Olesov; O. S. Kaganova; T. A. Fazilova; M. Z. Mirgazizov; A. A. Ilyin; I. A. Shugailov (Клиническая практика, 2019)
Background. According to the statistics, the incidence of dentoalveolar anomalies, as well as the frequency of orthodontic visits, is constantly growing.